DISTRIBUTION OF MACRO- AND MICRO-PLASTICS WITHIN THE BEACH ZONES OF INTERCONTINENTAL SEAS (CASE STUDY FOR YUZHNE CITY, UKRAINE) - YEMELIANOV, Volodymyr; NASIEDKIN, Yevgen; IVANIK, Olena; KUKOVSKA, Tamara; YUKHYMCHUK, Volodymyr; MYTROPHANOVA, Оleksandra (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Suburban beaches within the Ukrainian coast of the northwestern shelf of the Black Sea, taking into account the density of industrial and social infrastructure, the proximity to the confluence of large rivers with significant catchment areas into the sea, are indicative of objects for carrying out regulatory studies of the distribution of plastic waste and microplastics in the components of the environment . Methods. The regularities of the distribution of plastic waste and microplastics within the coastal zone of the north-western part of the Black Sea were determined using the example of test sites in the city of Yuzhne (Odesa region, Ukraine). To analyze the quantitative and qualitative characteristics of the synthetic material and to determine the features of its formation, distribution and accumulation in the coastal zone, the method of filtering water flows of the surface runoff was used. Visual analysis of plastic polymers was performed and their types were determined using spectroscopy and OPUS 7.5 software.Results. The results of Raman spectroscopy studies proved that the majority of selected samples of macro- and microplastics are represented by polypropylene, polyethylene and polystyrene. It has been confirmed that the main part of the plastic has a high migration capacity within the coastal areas, which is determined by the transport of runoff during periods of wave activity and the absence of a permanent component in the sand layer within the beach. It was determined that for different dimensional categories of plastic fragments, their species composition changes radically. Polymeric synthetic objects larger than 1 cm are represented mainly by polypropylene, polystyrene, and high-density polyethylene products. In the category of finer dimensions of plastic fragments, both the species spectrum of polymers and their belonging to different economic segments of use is expanding. Synthetic fibers, which make up the majority of objects of the smallest particle size fraction - less than 0.1 mm - are present everywhere and in significant quantitative composition.  Conclusions. Research shows that the parameters of the coastline (width, length, slope, shape, presence of vegetation, anthropogenic variability), hydrogen processes and the geological structure of the coastal zone have a significant impact on the formation of the conditions for the accumulation of plastics and microplastics. In order to further study the factors influencing the pollution of the beach area by plastic products and microplastics, monitoring studies are needed within the presented test areas.
Keywords: pollution; plastic waste; microplastic; Black Sea; coastal zone; lithodynamics